'I don't think racism is that bad any more': Exploring the 'end of racism' discourse among students in English schools. (31st August 2015) - Andreouli, Eleni; Greenland, Katy; Howarth, Caroline
Abstract: In this paper, we present findings on lay constructions of racism from a focus group study (11 groups, n = 72) with a mixed sample of secondary‐school students in England. We show that racism was, on the whole, 'othered': It was located in other times, places, and people or was denied altogether. We show that this way of talking about racism had different uses depending on the identity stakes involved in different interactional contexts. Even in the cases where racism was constructed as common, participants worked hard to make an 'irrefutable' argument, which suggests that they were anticipating reputational damage by making a claim for the persistence of racism. We discuss these findings with regard to the different levels of analysis involved in constructions of racism (micro‐interactional, local and broader normative context) and with regard to an 'end of racism' discourse that appeared to provide the normative framework for participants' accounts.